How do ownership concentration and family control affect R&D investments? New evidence from Taiwan - Irene, Wei Kiong Ting; Lo, Huai-Chun; Kweh, Qian Long (John Wiley & Sons Ltd., 2018)
This study finds a nonlinear relationship between ownership concentration and R&D investments. Specifically, ownership concentration is positively related to R&D investments at a low level of ownership concentration; the relationship becomes negative when ownership concentration is at a high level. However, the impact of ownership concentration on R&D investments is lessened in family-controlled firms; that is, family control moderates the relationship between ownership concentration and R&D investments. Overall, this study suggests that the ownership concentration’s nonlinear impact on R&D investments differs between family-controlled firms and non-family-controlled firms.